The Effect of FSLC Model with Crossword Media on Interest and Learning Outcomes - Desri Berliana Daeli; Ricky Andi Syahputra; Ani Sutiani; Iis Siti Jahro; Ratu Evina Dibyantini (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
The FSLC (Formulate Share Listen Create) model is a cooperative learning approach. This study compares the FSLC model with crossword media to a conventional PowerPoint-based model and examines the correlation between students' learning outcomes and interest. The sample included 25 purposively selected students per class for experimental and control groups with similar backgrounds. Using a pretest-posttest control group design, the experimental class learned electrolyte and nonelectrolyte solutions via FSLC with crossword puzzles, while the control class used PowerPoint. Results showed higher average interest (86.60 vs. 80.40) and outcomes (83.30 vs. 79.70) in the experimental group, with F_calculated > F_table. A strong correlation was found between interest and outcomes in the experimental class (r = 0.931 > r_table = 0.396), with a determination index of 11%, indicating a positive relationship.